DEVELOPMENT OF VOCABULARY ON KBBI I – ONLINE KBBI EDITION VI - Mulyono, Sugeng Edy; Zamroni, Mohammad; Hidayati, Nuril (JURNAL LITERASI, 2023)
Vocabulary are the important elements or the basic from a language that should be mastered in learning of a language.We will not be able to pronounce or write down of something if we don’t know or master of vocabulary. We will not be able to communicate and interact each other without master of vocabulary of a language.By the development of time and the development of language, the vocabulary of many languages should be developed because they need to use of that vocabularies. The vocabularies will be developed and will be continously developed for next time. There are many factors that caused why the vocabularies continously developed, they are:Education, Social and Culture, Economic, Technic, Information and Technology. the surrounding in our environment and there are many factors which influence of the development of vocabularies from the other languages. We are the academics and as the citizen should be participate in the folowing of the developmet of our language and the other languages to enriches and spread out of our knowledge and our mind to the development of vocabulary of the other language.In Indonesia KBBI is a media that accomodate vocabularies which has published until 6th Editon, they are Edition I – Online Edition.